Crouzon Syndrome-A Case Report - Malarmathi Eswaramoorthy; G. V. Murali Gopika Manoharan (Journal of Indian Academy of Oral Medicine and Radiology)
Crouzon syndrome is a hereditary condition with an autosomal dominant pattern, characterized by the premature synostosis of coronal and sagittal sutures. It ranks as the second most prevalent craniosynostosis syndrome and the results from mutation in FGFR-2 and FGFR-3. We present a case of a 5-year-old male child diagnosed with the Crouzon’s syndrome, who exhibited abnormal skull and facial characteristics, including craniosynostosis, protruding eyes, hypoplastic maxilla, and relatively prominent mandible. Timely diagnosis and intervention can enhance the patient’s quality of life, reduce the risk of complications like intracranial hypertension, and allow the individual to live a normal life.